PERBANDINGAN NILAI PARAMETER MARSHALL ASPAL MODIFIKASI BUTON NATURAL ASPHALT CRUMB RUBBER TYPE 1 (BNA CR1) 10% DAN BNA CR1 20% TERHADAP ASPAL PEN.60/70 - Muhammad Zaki; Sofyan M. Saleh; Mochammad Afifuddin (Prodi Magister Teknik Sipil Unsyiah, 2018)
here was an urgent need to accelerate the project duration in project MYC WIL.I-2C, however, inconsistent policy towards the predefined specification was taken by using 10% Buton Natural Asphalt Rubber (BNA-R), whereas the specification should be 20% BNA-R. The objective of this research is to compare the strength performance between BNA-R 1 10% and BNA-R 1 20%, compared to BNA-R1 0% (pen.60/70). The lab analysis was done in Jalan Raya Laboratory, Faculty of Engineering, Syiah Kuala University, Banda Aceh. The method that were used are Marshall method and durability at optimum asphalt content by using wet method. The results showed that stability value of BNA-R without substitutes was 1164 kg, BNA-R 10% was 1440 kg, and the highest was found in BNA-R 20% i.e. 1462 kg. Durability value without substitutes was 105.17%, whereas, durability of BNA CR 1 10% was 101.14% and BNA CR 1 20% was 100.81%. All Marshall parameters in BNA-R with and without substitutes, including stability, flow, MQ, density, VIM, VMA and VFA were still fulfill the specification set by the Directorate General of Highways (Bina Marga) rev 3 in 2014 and interim 3 rev 2 in 2015.